Formation of an Intracontinental Orogen Above the Permo-Triassic Mantle Convection Cell in the Paleo-Tethys Tectonic Realm due to Far-Field Stress Derived From Continental Margins - Zhao, Lei; Zhai, Mingguo; Zhou, Xiwen (Frontiers in Earth Science, 2022)
The identification of intraplate orogens seemingly poses challenges to the plate tectonic theory. Delineating the formation processes of intraplate orogens can provide clues for the better understandings of the above issue. Although still controversial, the Indosinian (Permo-Triassic) orogeny in the South China Block (SCB) is potentially a good example of intracontinental orogen. In this paper, we carry out studies on the Indosinian high-grade rocks in the northeastern Cathaysia Block of the SCB, hoping to cast light on the features and formation processes of intraplate orogenic belts. These rocks exhibit HP/HT granulite facies mineral assemblages and reaction textures imply that they witnessed eclogite-facies metamorphism. Their clockwise P-T trajectories with isothermal decompression stages suggest significant crustal thickening followed by quick orogenic collapse. Immobile whole-rock trace elements indicate basaltic protoliths features, resembling E-MORB and OIB, respectively. SIMS zircon U-Pb age dating confirms Indosinian metamorphic ages of ~248 Ma and a protolith age of ~953 Ma. The mantle-like O isotopic compositions of the Neoproterozoic magmatic zircon cores further attest that they were primarily mantle derived rocks. The whole-rock Sm-Nd isotopic compositions show more enriched features because of metamorphic alteration, while zircon Lu-Hf isotopic results show primitive characteristics with Neoproterozoic model ages. These features suggest that the high-grade mafic rocks, as well as the metamorphosed early Precambrian metasedimentary rocks hosting them, are all continental crust components and juvenile oceanic crust components featuring plate margins are absent during the SCB Indosinian orogeny. Characteristics of these high-grade rocks and their spatial occurrences are both consistent with the proposal of an intracontinental orogen. After summarizations and comparisons of the Indosinian plate margin activities around the SCB, we suggest that this northeast-southwest trending orogenic belt is geometrically consistent with two mantle convection cells, with one conveying the SCB northward to collide with the North China Craton, and the other conveying the Paleo-Pacific plate northwestwards to form an active continental margin along the southeast SCB. The driving mechanism of the formation of the SCB Indosinian intracontinental orogenic belt could have broad implications for other intraplate orogens around the world.